Volatile compounds and alkaloids from the aqueous extract of mitragyna speciosa and their in vitro and in vivo anti-inflammatory studies / Norsita Tohar - Norsita , Tohar (2016)
This work involved the aqueous extraction, supercritical fluid extraction (SFE) and hydro distillation extraction. Five compounds were isolated from the water extract and purified by using several chromatography techniques such as column chromatography (CC), thin layer chromatography (TLC) and preparative thin layer chromatography (PTLC). These compounds include mitragynine, speciociliatine, paynantheine, 3, 4, 5, 6-tetradehydromitragynine and 7-hydroxyspeciociliatine. The structures of these isolated compounds were elucidated with the aid of spectroscopic methods such as 1D NMR (1H, 13C, DEPT), 2D NMR (COSY, HMBC, HMQC/HSQC, NOESY), UV, IR, ESIMS/LCMS-IT-TOF and their data were compared with those in the literature. Fifteen compounds constituting 93.53% of the most active supercritical fluid (SCF) extract on nitric oxide (NO) inhibition have been identified. The prominent components were fatty acids, accounting for 39.01% of the total yield. The rest of the crude was made up of four hydrocarbons (36.67%), three phytosterols (9.32%), two esters (3.45%), two alcohols (2.30%) and a tocochromanol (2.78%). Palmitic acid (34.90%) was the most abundant compound followed by heptacosane (18.56%) and nonacosane (11.00%). Thirty-nine identifiable constituents of the essential oil that represented 85.29 ± 2.26% of the total peak area have been successfully characterized. Isophytol (23.51 ± 4.19%), (E)-phytol (9.17 ± 2.52%) and (2E, 6E)-farnesyl acetate (8.96 ± 2.54%) were among the major compounds. SFE extracts and the essential oil were analysed by means of gas chromatography and gas chromatography-mass spectrometry. The components of the extracts were identified by comparison using the NIST08s.LIB mass spectral database and their identifications were further confirmed through comparison with Kovats indices (I). The SFE and the aqueous leaves extracts were investigated in parallel with other solvent extracts for in vitro (NO inhibitory test) anti-inflammatory activity. M5S1 (the non-alkaloidal SFE crude) showed the highest NO inhibitory activity at 60.08 ? 10.02% without any cytotoxicity effect (cell viability, 91.98 ? 11.58%). Parameters for the extraction of M5S1 (extracted using pure SCF-CO2 at 3000 psi of pressure and temperature at 60oC) are determined as the optimal SFE condition to furnish the extract that possesses the highest anti-inflammatory activity without any toxicity. This finding provides the first evidence that the non-alkaloidal extract of the leaves of M. speciosa that possesses NO inhibitory potential. The aqueous extract of the leaves of M. speciosa, MSEA was further investigated for its in vivo (anti-ulcer test) anti-inflammatory activity. In comparison to ulcer control group, the animals pre-treated with MSAE showed significant reduction in gastric injuries grossly and histology. The gastric homogenate of the animals pre-treated with MSAE showed considerable decrease in the malondialdehyde (MDA) level, increased superoxide dismutase (SOD) activity and also protein concentration. Immunohistochemistry of these trial groups showed over-expression of heat-shock protein 70 (HSP70) and down-expression of pro-apoptotic BAX protein. In addition, the MSAE treated animals revealed significant increment in the pH of the stomach content. Acute toxicity study of the aqueous extract was safe up to 1000 mg/kg. This research provided first gastric protecting evidence of M. speciosa aqueous leaf extract as evaluated by biochemistry, histology and immunohistochemistry studies. Results of the present study indicate that both extracts, M5S1 and MSAE have potential property in preventing inflammatory diseases.